2017
DOI: 10.3171/2017.6.focus17251
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity and the brain connectome: what can Jean Talairach’s reflections bring to modern psychosurgery?

Abstract: Contrary to common psychosurgical practice in the 1950s, Dr. Jean Talairach had the intuition, based on clinical experience, that the brain connectome and neuroplasticity had a role to play in psychosurgery. Due to the remarkable progress of pharmacology at that time and to the technical limits of neurosurgery, these concepts were not put into practice. Currently, these concepts are being confirmed by modern techniques such as neuroimaging and computational neurosciences, and could pave the way for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Stereotactic surgical methodology was first described in the late 19th century (Apra et al, 2016), but applications in neurological diseases on the basis of neurophysiological principles started only in the second half of the 20th century (Giller et al, 2017; Bourdillon et al, 2018). Performing a lesion on deep mesencephalic or diencephalic small structures with wide projections on large cortical areas was exciting perspectives in psychiatric and neurological fields and drastically reduced the morbidity of the surgical procedures (Miocinovic et al, 2013; Bourdillon et al, 2017). These lesional procedures were indicated in pathologies producing positive signs (like tremor or dystonia) but were useless in pathologies in which negative signs were preponderant, such as disorder of consciousness (DoC).…”
Section: Invasive Electric Stimulationmentioning
confidence: 99%
“…Stereotactic surgical methodology was first described in the late 19th century (Apra et al, 2016), but applications in neurological diseases on the basis of neurophysiological principles started only in the second half of the 20th century (Giller et al, 2017; Bourdillon et al, 2018). Performing a lesion on deep mesencephalic or diencephalic small structures with wide projections on large cortical areas was exciting perspectives in psychiatric and neurological fields and drastically reduced the morbidity of the surgical procedures (Miocinovic et al, 2013; Bourdillon et al, 2017). These lesional procedures were indicated in pathologies producing positive signs (like tremor or dystonia) but were useless in pathologies in which negative signs were preponderant, such as disorder of consciousness (DoC).…”
Section: Invasive Electric Stimulationmentioning
confidence: 99%
“…developed a strong interest in the mapping of brain networks through his primary interest in psychiatry. 3 Therefore, when Talairach got involved in epilepsy research, he imagined a stereotactic methodology allowing prolonged intracranial electroencephalography (EEG) for recording epileptic networks, namely stereoelectroencephalography (SEEG). He developed this procedure with Gabor Szikla, and the use of angiography to maximize vascular safety by preventing damage to blood vessels was an obsession.…”
mentioning
confidence: 99%
“…Currently, another technique has been designed to improve the accuracy of DBS, called closedloop deep brain stimulation (CL-DBS), which uses studies of the complete connection that occurs from one point to another point in the brain through neural pathways, called a connectome. [49][50][51] One of the advantages of DBS, when compared to other surgical procedures, is its reversibility. 12 Studies have also reported its benefit in reducing recurrence rates, decreasing the intensity of residual psychosis, and improving cognitive impairment by reducing the negative symptoms.…”
Section: Discussionmentioning
confidence: 99%